Retail Competition in the U.S. Electricity Industry - Hughes, John (Maine Policy Review, 1994)
The ever-increasing competitive nature of the electric utility business has been lent additional impetus by federal policies that mandate restructuring of the industry. John Hughes, writing from the perspective of large industrial consumers, offers a vision for restructuring the electric utility industry. He frames his vision in response to goals outlines in the California Public Utilities Commission’s proposal to restructure that state’s electric utility industry
Keywords: electric utilities; electricity industry